Pengaruh Brand image, Religiusitas dan Lokasi terhadap Keputusan Menjadi Nasabah Bank Syariah (Studi kasus pada mahasiswa Universitas Al-Amien Prenduan) - Mashuri Toha; Ilham Maulana; Alfani Mubarak; Moh. Bahij Al-Ardani (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2024)
This research aims to analyze the influence of brand image, religiosity and location on the decision to become a sharia bank customer among students at Al-Amien Prenduan University. Brand image, as a consumer's perception of a brand, is considered capable of forming trust and loyalty, while religiosity plays an important role in decision making based on sharia principles. Location is also considered to influence accessibility and comfort for potential customers. Data was collected through an online survey using Google Form, with respondents selected purposively from student students who were not yet sharia banking customers. Data analysis was carried out using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to test the relationship between variables and identify direct and mediating effects. The research results show that brand image has the most significant influence on the decision to become a customer, both directly and as a mediator between religiosity and the decision. Religiosity was also proven to have a positive effect on brand image, but location did not show a significant influence on the decision to become a customer, which could reflect a shift in consumer preferences towards digital banking services. This research suggests that Islamic banks need to focus on strengthening branding strategies that reflect religious values and developing better digital services to attract and retain customers. These results provide an important contribution to the literature on Islamic bank marketing and the development of more effective marketing strategies.